Portuguese Version of the Intentional Non-Adherence Scale: Validation in a Population of Chronic Pain Patients - Sampaio, Rute; Cruz, Mariana; Pinho, Simão; Dias, Cláudia Camila; Weinman, John; Castro Lopes, José M. (Frontiers in Pharmacology, 2021)
Objective: Despite the effectiveness of pain medicines, non-adherence to prescribed medication remains a major problem faced by health care systems. The aim of present study was to perform the translation, cultural adaptation and validation of the Intentional Non-Adherence Scale (INAS) for the European Portuguese language in a sample of chronic pain patients. Methods: A Portuguese version of INAS scale was constructed through a process of translation, back translation, and expert’s panel evaluation. A total of 133 chronic pain patients were selected from two Chronic Pain Clinics from tertiary hospitals in Porto, Portugal. The protocol interview included the assessment of pain beliefs (PBPI), beliefs about medicine (BMQ), medication adherence (MARS-P9) and two direct questions about adherence previous validated. Results: The Internal consistency was excellent in all subscales: α=0.902 for Testing Treatment α=0.930 for Mistrust treatment; α=0.917 for Resisting treatment; and α=0.889 for Resisting illness. Exploratory and confirmatory factor analysis revealed a four-factor structure that explained 74% of the variance. The construct validity of the INAS was shown to be adequate, with the majority of the previously defined hypotheses regarding intercorrelations with other measures confirmed. Conclusion: Portuguese version of INAS could be a valuable and available instrument for Portuguese researchers and clinicians to assess the intentional non-adherence determinants during the management of chronic pain.